2000
DOI: 10.1074/jbc.275.7.4654
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Staphylococcus aureusNADPH-dependent Enoyl-Acyl Carrier Protein Reductase by Triclosan and Hexachlorophene

Abstract: Enoyl-acyl carrier protein reductase (FabI) plays a determinant role in completing cycles of elongation in type II fatty acid synthase systems and is an important target for antibacterial drugs. The FabI component of Staphylococcus aureus (saFabI) was identified, and its properties were compared with Escherichia coli FabI (ecFabI). ecFabI and saFabI had similar specific activities, and saFabI expression complemented the E. coli fabI(Ts) mutant, illustrating that the Gram-positive FabI was interchangeable with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
168
1
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(178 citation statements)
references
References 25 publications
(45 reference statements)
6
168
1
3
Order By: Relevance
“…Studies with a des-hydroxyl analog of triclosan showed a more than 10,000-fold reduced affinity for E. coli ENR and implicated a critical antibacterial role for the triclosan 2-hydroxy group (55). Moreover, it was proposed that the ether oxygen of triclosan might be critical to the formation of the ternary complex, because corresponding 2-hydroxydiphenylmethanes did not result in tight binding (59), whereas the replacement of the ether oxygen with sulfur abolished the inhibitory activity (21). Ring B of triclosan was considered to be of minor importance, because variations in this region had less effect on inhibitor activity.…”
Section: Resultsmentioning
confidence: 99%
“…Studies with a des-hydroxyl analog of triclosan showed a more than 10,000-fold reduced affinity for E. coli ENR and implicated a critical antibacterial role for the triclosan 2-hydroxy group (55). Moreover, it was proposed that the ether oxygen of triclosan might be critical to the formation of the ternary complex, because corresponding 2-hydroxydiphenylmethanes did not result in tight binding (59), whereas the replacement of the ether oxygen with sulfur abolished the inhibitory activity (21). Ring B of triclosan was considered to be of minor importance, because variations in this region had less effect on inhibitor activity.…”
Section: Resultsmentioning
confidence: 99%
“…394 Recent studies suggest that this agent's antibacterial activity is attributable in large part to binding to the active site of enoylacyl carrier protein reductase. 395,396 Triclosan has a fairly broad range of antimicrobial activity ( Table I.11.7), but tends to be bacteriostatic. 48 Minimum inhibitory concentrations (MICs) range from 0.1 to 10 μg/ ml, while minimum bactericidal concentrations are 25-500 μg/ml.…”
Section: Triclosanmentioning
confidence: 99%
“…433,434 Very high MICS for triclosan were reported by Sasatsu and colleagues, 438 and the description of a triclosan-resistant bacterial enzyme has raised the question of whether resistance may develop more readily to this agent than to other antiseptic agents. 396 Under laboratory conditions, bacteria with reduced susceptibility to triclosan carry crossresistance to antibiotics. 439,440 Reduced triclosan susceptibility or resistance was detected in clinical isolates of methicillinresistant S. epidermidis and in MRSA, respectively.…”
Section: Reduced Susceptibility Of Microorganisms To Antisepticsmentioning
confidence: 99%
“…PfENR is known to be an important target for the development of antimicrobial and antiparasitic molecules (11)(12)(13)(14)(15). We have reported earlier that triclosan, a microbicide and a common additive in many household items, strongly inhibits PfENR with high potency and also exhibits slow-tight binding mechanism in presence of catechins (16,17).…”
Section: Introductionmentioning
confidence: 99%